(3OQGSGJ aj GdJYdje GdLGeYj (B:s (3eLdI OhQjI eMceI eJNUUI (B/s - (3LGeYI Yjf TeS(B.s (3eQcR JWhjQ GdJYdje GdLGeYjs ([(3GdbGgQI(B] :s (3LGeYI Yjf GdTeS, cdjI GdJQHjI, eQcR JWhjQ GdJYdje GdLGeYjs)
(3aj GdJYdje GdYGdj(B.s
(3BNQ YOO Je GdQLhY Edjg(B: (3Y(B24(2013)s
(3WQjbI GdhUhd (B: (3THcI GdEfJQfJ(B.s
(3GdhUa eCNhP ef (B: (3GdeLdO (B29(3, GdYOO (B29 ((3GdTJGA (B2015)s
(3BNQ YOO Je JOGhdg (B: (3GdeLdO (B49(3, GdYOO (B49 ((3GdNQja (B2020)s
(3JGQjN GdGWdGY (B: 30 / 12 / 2020.s
Keywords: (3GdJYdje GdYGdjs -- (3OhQjGJs; (3GdJYdjes -- (3OhQjGJs